Analisis Dampak Penggunaan Media Pembelajaran Kotak Berjalan Dan Bintang Bernilai Pada Hasil Pembelajaran IPS DI Kelas 5 SDN 158054 Mombang Boru 2 Kabupaten Sibabangun - Wida Bonor Gultom, Julia ivanna (Journal of Educational Research and Humaniora (JERH), 2023)
In the learning process, teaching sometimes feels boring because the learning that is carried out feels monotonous and boring, especially in social studies learning which discusses history and stories that make students especially students feel sleepy. So the formulation of the problem to be examined is how the learning process can be effective and fun the role of using conventional learning media in the form of walking boxes and valuable stars that can make learning fun and educative. The purpose of this lesson is to make students active and show that social studies learning can be fun. This research method is field research with a descriptive approach qualitative.